LEARNING MORE FROM PATTERNS OF GAIT SPEED DURING THE 400-METER WALK. (11th November 2018) - Urbanek, J; Wanigatunga, A A; Di, J; Simonsick, E M; Zipunnikov, V; Schrack, J A
Abstract: Time to finish the 400-meter (T400m) walk is a powerful measure of fitness and function. However, patterns of slowing or speeding up during the test, while typically ignored, may provide additional information. Lap split times were collected during a fast-paced10-lap 400-meter walk in 1299 participants of the Baltimore Longitudinal Study of Aging. For each lap, average gait speed (m/s) was calculated, resulting in 10-measures per participant. K-means clustering were used to identify 5 prevailing patterns. Clusters were modeled as a categorical covariate in linear regression models with endurance, aerobic capacity, and fatigability outcomes adjusted for age, sex, BMI and T400m. Patterns were differentially associated with endurance (p<0.001), aerobic capacity (p<0.001) and mobility (p<0.001). Those demonstrating the greatest speed recovery in the final laps (J-or-U-shaped clusters) had the best performance across all outcomes. Analysis of patterns provides a new dimension for analyzing the 400-meter walk by illuminating meaningful characteristics of performance.